Potensi Masalah Pinjaman Online Akibat Ilitrasi Keuangan : Indonesia - Syara Purnama Sari; Lailatul Qodri (Penerbit Goodwood, 2025)
Purpose: The objectives of this study are: to examine the influence of financial literacy on financial attitudes, financial literacy on self-efficacy, financial attitudes on financial skills, self-efficacy on financial skills and financial skills on financial behavior. Methodology: This research is a quantitative research. The data source used in the research process is primary data. The population in this study is all Micro, Small and Medium Enterprises (MSMEs) in Lampung Province. Sampling in this study uses the purposive sampling method with the following criteria: 1. MSMEs that have been run for at least 6 months, 2. MSMEs that sell food and beverages, 3. MSMEs whose source of funds comes from online loans. Using the Slovin formula, the sample used was 200 respondents. Statistical tests use AMOS 24 with the Structural Equation Model (SEM) approach. Result: The results of the study showed that financial literacy had an effect on financial attitudes, financial literacy had an effect on self-efficacy, self-efficacy had an effect on financial skills and financial skills had an effect on financial behavior. While financial attitudes have no effect on financial skills. Conclusion: The Financial Literacy variable has an effect on the Financial Attitude variable, the Financial Literacy variable has an effect on the Self-Efficacy variable. Limitations:. The sample of this study is only limited to food and beverage MSMEs in Lampung Province, it is hoped that future research can use a wider and more sample. Contribution: The impact for MSMEs due to low financial illiteracy is difficulties in making financial statements, conducting financial records and managing debts. As a result, many MSMEs are often late in paying and are subject to fines. Even if MSMEs are unable to pay the loan, they will be included in the Financial Services Authority (OJK) blacklist.